Fostering the institutional repository through policies and interoperability with online services: the case of La Plata National University - Villarreal, Gonzalo Luján (2015)
This article presents the work being done by La Plata National University (Universidad Nacional de La Plata, UNLP) to ensure both the preservation and dissemination of its academic and scientific output. To this end, the university has established a combination of institutional policies, workflows among departments, and services and sofware developments for its programs and projects. Developments focused on importing and exporting metadata between DSpace – the sofware used by the UNLP main repository – and OJS/OCS – used by its Journals Portal and Conferences Portal – and integrating repository assets into the most common content management systems (CMSs) used by institution parties, such as WordPress and Joomla! Te first results of four years of back-and-forth collaboration show an important growth in size, rankings, usage, and the online visibility of the whole university.